DESIGNING AN ENCRYPTION FUNCTION FOR CHAOTIC-BASED MODEL WITH BIFURCATION SHIFTING IN SECURITY COMMUNICATE - ALIWI, BUSHRA HUSSIEN (Journal of Duhok University, 2023)
A new design for a function(s) developed in the encryption stage on secret communications by shifting of the bifurcation for Quadratic map that is chaotic with one parameter. These functions approach the values for parameters on the real axis. Each new value for a chaotic map will add to the generated real values super increasing sequence toward negative infinity, and then modify the ciphertext. Bifurcation shifting computed through different functions shifting the bifurcation function such as triangular and exponential function. A modified ciphertext applied in the terms of a fuzzy chaotic based model. This encryption stage will be applied in communication models or as a part of the master-slave system. Then we provide the algorithms to recover the performance steps of the designed method. Finally, the process of numerical implementation is discussed to verify the effectiveness of the method with primary results.